2015
DOI: 10.1890/14-2476.1
|View full text |Cite
|
Sign up to set email alerts
|

Local and landscape effects in a host–parasitoid interaction network along a forest–cropland gradient

Abstract: Land-use driven habitat modification is a major driver of biodiversity loss and impoverishment of interaction diversity. This may affect ecosystem services such as pollination and biological control. Our objective is to analyze the effects of local (nesting environment: farms vs. tree stands) and landscape (forest-cropland gradient) factors on the structure and composition of a cavity-nesting bee-wasp (CNBW) community, their nests associates (henceforth parasitoids), and their interactions. We set up 24 nest-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(136 reference statements)
2
16
0
1
Order By: Relevance
“…Since parasitoids tend to have high levels of trophic specialization (Hawkins, 1994; Jeffs & Lewis, 2013; Poulin et al, 2011), we might expect a high correspondence between host and parasitoids communities. Thus, former studies conducted in contrasted habitat types also showed a high dependency of the community structure of the higher trophic level on the lower trophic level (Albrecht et al, 2007; Ebeling, Klein, Weisser, & Tscharntke, 2012; Osorio et al, 2015; Weiner, Werner, Linsenmair, & Blüthgen, 2014). However, and again refuting our second hypothesis, we did not find a strong matching in species composition between hosts and parasitoids across space, indicating that host‐parasitoid systems can be less specialized than previously thought (Blüthgen et al, 2007; Fontaine et al, 2009; Price, 1997; Schowalter, 1996).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since parasitoids tend to have high levels of trophic specialization (Hawkins, 1994; Jeffs & Lewis, 2013; Poulin et al, 2011), we might expect a high correspondence between host and parasitoids communities. Thus, former studies conducted in contrasted habitat types also showed a high dependency of the community structure of the higher trophic level on the lower trophic level (Albrecht et al, 2007; Ebeling, Klein, Weisser, & Tscharntke, 2012; Osorio et al, 2015; Weiner, Werner, Linsenmair, & Blüthgen, 2014). However, and again refuting our second hypothesis, we did not find a strong matching in species composition between hosts and parasitoids across space, indicating that host‐parasitoid systems can be less specialized than previously thought (Blüthgen et al, 2007; Fontaine et al, 2009; Price, 1997; Schowalter, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies working with cavity‐nesting bees and wasps analyze composition differences between seasons, habitats, or environmental gradients (Albrecht, Duelli, Schmid, & Müller, 2007, Tylianakis, Tscharntke, & Lewis, 2007, Osorio, Arnan, Bassols, Vicens, & Bosch, 2015, Osorio‐Canadas et al, 2018, Morris et al, 2014, Staab et al, 2016; review in Staab et al, 2018). Conversely, our study was conducted across a habitat that can be considered uniform (at a landscape scale), with no physical barriers or strong environmental gradients and dominated by a single vegetation type, and addresses spatial variability at a local scale (distance between plots is ca.…”
Section: Introductionmentioning
confidence: 99%
“…These findings also support general biodiversity‐ecosystem functioning theory (Cardinale et al., ) and the emerging hypothesis that bottom‐up effects of plant diversity on higher trophic levels already occur at small spatial scales (Albrecht et al., ; Ebeling et al., ; Fabian et al., ). Differing flower availability also explains why bees usually numerically dominate trap‐nesting communities in open landscapes (e.g., Osorio et al., ; Steckel et al., ), while in closed forests, wasps are more abundant (e.g., Staab et al., ; Stangler, Hanson, & Steffan‐Dewenter, ).…”
Section: Discussion and Summary Of Literaturementioning
confidence: 99%
“…Nevertheless, representing organisms in a high trophic level and thus being especially sensitive to environmental change, direct influences of landscape variables such as habitat isolation and fragmentation (e.g., Schüepp, Herrmann, Herzog, & Schmidt-Entling, 2011), forest cover (e.g., Klein et al, 2006) or plant diversity (e.g., Staab et al, 2016; following the enemies hypothesis: Root, 1973) on parasitoids have been shown. Landscape variables not only influence parasitoid diversity but also host-parasitoid interaction networks, which are usually simpler and less stable in more intensively used landscapes (Osorio et al, 2015;Tylianakis et al, 2007). Conversely, habitat restoration can increase the stability of host-parasitoid interactions in trap nests (Albrecht et al, 2007) (Matos et al, 2013;Stangler et al, 2015).…”
Section: Landscape and Community Ecologymentioning
confidence: 99%
See 1 more Smart Citation